China : Air Pollution and Acid Rain Control - The Case of Shijiazhuang and the Changsha Triangle Area - World Bank (Washington, DC, 2014)
This study, and the associated technical assistance project, has three main objectives. The first is to help localities in China address several questions related to the planning, and implementation of SO2 emissions, and acid rain control: What are the environmental consequences, specifically for localities of different pollution control strategies, in terms of the impacts on human health, agricultural productivity, and other sectors and activities? What are the relative costs of different sulfur emission reduction plans? Will the proposed strategies enable localities to meet the environmental targets set by the central government? The second objective is to assist with capacity building, and training in China. to enable cities and regions to carry out environmental, and economic analyses of sulfur emission impacts, and control programs. The third objective is to provide a forum for discussion with the central government, primarily the State Environmental Protection Administration (SEPA), on the results of the case studies, and the implications for national policy with respect to sulfur control. This study analyzes China's national sulfur pollution control program, looking at local implementation plans, and actions for reducing sulfur emissions in two municipalities- Shijiazhuang and Changsha. The city of Shijiazhuang in Hebei Province was chosen for a case study on ambient SO2 pollution control, representing a northern Chinese city, while the tri-city region of Changsha, Zhuzhou, and Xiangtan in Hunan Province, was chosen to represent a southern area experiencing serious levels of acid rain. The clear divide between northern and southern cities and regions, indicate that emission control efforts in the north will benefit from access to significant quantities of low sulfur coal, the lack of which in the south, will significantly increase the cost of sulfur emission control. Other findings suggest that gaining a better scientific understanding of the impacts of sulfur emissions, and improving estimates of the relative benefits of different control options, are two important pieces of information for leveraging local implementation efforts. While promoting policies with multiple benefits, is an effective way of cutting sulfur pollution without reliance on regulatory policies, or institutions.